Implementasi Algoritma Zhu Takaoka Pada Aplikasi Olshop Kamera Digital - Sri Sugiarti; Berto Nadeak (JURIKOM (Jurnal Riset Komputer), 2020)
A brand can reflect a product, but also has another dimension that is able to distinguish it from other products and is designed to meet the same needs. Digital cameras are devices for making images of objects for refraction through lenses on CCD sensors and more recently on BSI-CMOS (Back Side Illuminated) sensors that are more power efficient for more sophisticated cameras whose results are then recorded in digital format to in digital save media. The development of an era when someone more often captures his life's journey by expressing every activity into a photo using a digital camera because with that process can be done easily and good results for a photo that can capture the journey of one's life. With the increasing time of digital camera users more and more and digital camera brands are also increasingly sold in markets such as malls or shops, but to go to malls or shops will require transportation costs and not everyone has a free time to see new digital camera brands to the mall or shop because of its many work activities and other things. To overcome these problems the author builds an application that is the Implementation of the Zhu-Takaoka Algorithm in the Digital Camera Olshop Application. The zhu-takaoka algorithm is a string matching algorithm that can search words by shifting characters using 2 (two) dimensional arrays. The core process of searching for the zhu-takaoka algorithm is to search for words using the Right-to-left scan rule technique. Each shift in the word search process is determined by the shift values in the Good Suffix Shift Rule and Bad-Charcter Shift Rule tables. The expected results of this research are that it can help someone who wants to have a digital camera see or search for a digital camera brand using an Android application so that it can be done anywhere without having to go to the mall or shop.